Experimental evolution of bacterial survival on metallic copper. Issue 8 (22nd August 2022) - Xu, Feng; Liu, Sha; Naren, Naran; Li, Lily; Ma, Luyan Z.; Zhang, Xue‐Xian
Abstract: Antimicrobial copper‐containing surface materials have a great potential of reducing the risks of healthcare‐associated infections (HAIs), but their increased use in hospital facilities may select copper‐resistant strains, causing concerns to antimicrobial resistance management. Here, we describe a long‐term bacterial evolution experiment wherein a non‐pathogenic Pseudomonas strain was subjected to daily transfer in laboratory media with and without copper‐mediated contact killing. The copper treatment sequentially involved two surface materials differing in Cu content and thus contact killing effectiveness: first on brass (Cu 63.5%) and then on pure copper (Cu 99.9%). A gradual increase in bacterial survival rate (or a decrease of killing effectiveness) was observed over time on the related copper surfaces. For the final evolved populations after 320 transfers, 37.8% cells of the copper‐evolved populations were able to survive 60 min on pure copper, whereas populations in the control lines remained sensitive with a survival rate of 0.09% under the same contact killing condition. Genome re‐sequencing revealed 540 mutations accumulated in the copper lines but only 71, on average, in the control lines (variant frequency > 0.5). The mutagenic activities of Cu + ions were confirmed by measuring spontaneous mutation rate in a laboratory medium supplemented with copper sulfate at a non‐inhibitory concentration. The copper‐evolved populations have acquired increased resistance to Cu + ions and tobramycin (an aminoglycoside antibiotic), but showed decreased production of biofilm, exoprotein, and pyoverdine. Together, our data demonstrate the potential of bacteria to evolve prolonged survival on metallic copper, and the long‐term impacts should be considered with increased copper usage in hospital environments. Abstract : A non‐pathogenic bacterial strain was subjected to daily transfer in laboratory media with and without copper contact killing. Results of this long‐term evolution experiment revealed the potential of bacteria evolving prolonged survival on metallic copper surfaces. Mitigation strategies such as regular surface cleaning is thus required with the increased use of antimicrobial copper surface materials in the hospital environments.